Laterality of Rhegmatogenous Retinal Detachment - Sevillano, Carlos; Viso, Eloy; Moreira-Martínez, Santiago; Parafita-Fernández, Alberto; Sampil, Marta; Blanco, María José (Journal of Ophthalmology and Research, 2021)
Introduction: Retinal detachment (RD) is a potentially blinding disease. The epidemiological characteristics of this disorder could help to understand the factors influencing its incidence.</p Purpose: To investigate the laterality of rhegmatogenous retinal detachment (RRD) and the differences between right and left eyes. Methodology: All RRD cases in Pontevedra from 2008 to 2014 were retrospectively analyzed. The epidemiological characteristics of them were investigated. Results: The right eye (P=0.035) was most frequently involved (55.5%) with more detached macules (P=0.016). No ocular differences were found between right and left eyes but ocular hypertension, being the left eye more affected (P=0.039). Conclusions: The right eye is more and worse involved than the left eye. The solar radiation effect on the eye might be one important factor.